Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If tana=(1+2^-x)^-1,. tanb=(1+2^(x+1))^-1then. A+b=

If tana=(1+2^-x)^-1,. tanb=(1+2^(x+1))^-1then. A+b=

Grade:11

2 Answers

Ayanava Datta
40 Points
3 years ago
answer of the question is 45
hint=find tan(a+b) 
put the value tana ‘tanb
and slove
got tan[a+b]=1
[a+b]=1
 
Arpit Sahu
13 Points
3 years ago
Tan(a+b)=tana + tanb/1-tanatanb
 =(1+2^-x)^-1 + (1+2^x+1)^-1/1-(1+2^-x)^-1.(1+2^x+1)^-1
 =1+2^x+1+2^-x-1 / 1-(1+2^x)(1+2^-x-1)
=[(2^x+2 + 2^2x+1 + 1)/2^x+1]/[(2^2x+1 + 2^x+1 +1)/2^x+1]
=1
=45°
=π/4

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free